Effectiveness of the Station Rotation Blended Learning Model in Mastering Mufradat - Hidayat, Rahmat; Siyam, Fera Favirotus; Muhammad Wahyudi; Annisa Avilya (Arabiyatuna: Jurnal Bahasa Arab, 2025)
This study examines the effectiveness of the station rotation blended learning (BL) model in enhancing the mastery of mufradat (Arabic vocabulary) among Grade VII students at MTs Anwar Futuhiyyah Yogyakarta. The research was motivated by the low vocabulary mastery among students, attributed to limited instructional time and a lack of innovation in Arabic language teaching. To address this, the researcher introduced a station rotation BL model designed to promote student engagement and deepen vocabulary understanding. The study employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group. The sample consisted of 16 students from classes 7A and 7B, selected through simple saturated sampling. The Mann–Whitney test results showed no significant difference in pre-test scores between the control and experimental groups (p = 0.954 > 0.05), indicating comparable initial proficiency. Post-test results analyzed with an Independent Sample T-Test also showed no significant difference between the two groups (p = 0.097 > 0.05), suggesting that the station rotation BL model did not significantly improve students’ vocabulary mastery. Based on these findings, it is recommended that teachers explore alternative instructional models to enhance mufradat acquisition at MTs Anwar Futuhiyyah.